Dinoflagellate cyst composition, abundance and horizontal distribution in Bolinao, Panagasinan - Baula, Iris U.
This study provides baseline data on dinoflagellate cysts in Bolinao, Pangasinan. Cysts as part of the dinoflagellate life cycle are important in understanding bloom dynamics of harmful microalgae. Surface sediment samples have been collected from 54 stations in October 2006 and 5stations were monitored from 2004 to 2006. Samples have been processed palynologically and fluorescent techniques applied. Exploratory data analysis using Two Way Indicator Species Analysis (TWInSpAn) has been done to identify major patterns of distribution and Canonical Correspondence Analysis (CCA) ordinated stations and species along sediment, environmental and hydrographical variables to determine spatial variations in community structure. Thirty-nine cyst types have been identified and among them is the toxic species, Alexandrium minutum. Species richness and diversity correlated with slit, mud, carbonates and depth but have been observed to be generally low in the area (p>0.05). Multivariate analysis shows that sediment grain size, nutrients and water depth are important variables related to cyst distribution. Two accumulation points that can be source and sinks of blooms have been identified and explained by bottom sediment transport from grain size trend analysis. The decrease in species richness and diversity of dinoflagellate cysts from 2005 to 2006 has been attributed to intensive mussel farming. Heterotrophs have been dominated during the northeast and southwest monsoon seasons while autotrophs which included A.minutum, have dominated during tradewinds. Results indicate that the presence of systs accumulation points could possibly seed blooms during tradewinds and thus should be monitored effectively to prevent negative public health impacts.